Digital Literacy and Employee Performance in Culinary MSMEs: A Mediation Model - Hima Barima (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the mediating role of competency in the relationship between digital literacy and employee performance among culinary micro, small, and medium enterprises (MSMEs) in Purbalingga Regency, Indonesia. Digital transformation has encouraged culinary MSMEs to adopt social media marketing, digital payment systems, online delivery platforms, and customer communication applications. However, the effectiveness of these technologies depends on the ability of owners and employees to use them productively. This study employed a quantitative explanatory design involving 150 culinary MSME owners and employees who had experience using digital tools in daily business operations. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that digital literacy has a positive and significant effect on competency and employee performance. Competency also has a positive and significant effect on employee performance and partially mediates the relationship between digital literacy and employee performance. These findings show that digital literacy improves employee performance both directly and indirectly through competency development. The study contributes to Human Capital Theory and competency-based human resource management by explaining how digital capability is transformed into work performance. Practically, the findings suggest that culinary MSME owners and local stakeholders should integrate digital literacy training with competency-based development programs to improve employee performance and business competitiveness.